Quantum Sensors for High-Precision Electrical Engineering Applications - Rizwan Tariq; Mahir Aabid Salman (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
Quantum sensing technologies are revolutionizing precision measurements in electrical engineering by leveraging quantum phenomena to achieve unprecedented accuracy. This paper examines the applications of quantum sensors in electric field detection, biomedical instrumentation, and power grid monitoring. The study explores their ability to enhance sensitivity, minimize noise interference, and improve real-time data acquisition. Through advanced quantum principles, these sensors enable high-resolution diagnostics in medical devices, optimize energy efficiency in smart grids, and enhance electromagnetic field measurements. The findings highlight the transformative potential of quantum sensors in modern engineering applications, paving the way for smarter and more efficient monitoring systems.